The Management of Santri Character Development at Pondok Pesantren Al-Luqmaniyyah - Nurul Istiqamah; Nurtanio Agus Purwanto (AIBPM Publisher, 2020)
Al-Luqmaniyyah is a pesantren (Islamic boarding schools) preserving the salaf tradition. Located in the middle of a city with most of its santri (students) are college students, undoubtedly it is exposed to a lot of globalization, while its younger students remain unable to filter the profound and devastating impacts. This study aims to determine how the management of character development of santri at Pesantren Al-Luqmaniyyah uses the four functions of management by George R. Terry. The method used is a qualitative approach with descriptive analysis. The results showed that Pesantren Al-Luqmaniyyah used the four management functions of George R. Terry in building the character of santri, including planning, organizing, actuating, and controlling.